Three dimensional modeling of thermal and structural analysis of roller compacted concrete dam - Abdulrazeg, Aeid Ali; Noorzaei, Jamaloddin; Bayagoob, Khaled Hamood; Jaafar, Mohd Saleh; Mohammed, Thamer Ahmed (2010)
Cracking due to thermal stress is one of the most important problem arising during the consecution phase in roller compacted concrete dams. This phenomenon is due to cement hydration, and environmental boundary condition which introduce thermal gradients in the dam body. The present investigation an attempt is made to develop a three-dimensional finite element code for coupled thermal and structural analysis of roller compacted concrete dams. The crack development within the dam body has been assessed using the proposed crack index. Finite element results have shown that, the higher temperature zone is the centre of the dam body with maximum predicted temperature of 42 0C, which gradually decreased to reach approximately the air temperature at the boundaries. The tensile stress developed in the dam body rang is 1.0 and 5.0 Mps.